Η ΜΑΘΗΜΑΤΙΚΗ ΠΑΙΔΕΙΑ ΚΑΙ Η ΟΡΟΛΟΠΑ ΤΗΣ ΣΤΟ ΒΥΖΑΝΤΙΟ ΚΑΤΑ ΤΟΝ ΒΙΕΝΝΑΙΟ ΕΛΛ. ΦΙΛ. ΚΩΔ. 65 (φ. llr-126r) - ΧΑΛΚΟΥ ΜΑΡΙΑ (Eoa kai Esperia, 2003)
In this article we present some few results of our study on the mathematicalcontent of the unpublished part (f. 11 r-126r) of Cod. Vind. Phil. gr. 65 (the other parthas been published by H. Hunger and K. Vogel), which is the subject of our Dr. thesis(to be submitted). This 15th century Byzantine MS includes the solution of problemsof practical arithmetic, geometry and algebra, the roots of which can be traced back toantiquity. Most of them are related to practical human needs and therefore they couldbe used not only by practical men like merchants, metal workers, builders and otherpeople but also by state employers to calculate taxes. The mathematical terminologyused in this MS has been strongly influenced by latin works; nevertheless itscomparison with modern Greek mathematical terminology reveals -apart from somedifferences- many identities and similarities showing the continuity of Greek mathematicaltradition through the centuries.